TEACHING EMOTIONAL ENGLISH INTONATION - Natalia Mospan (Borys Grinchenko Kyiv Metropolitan University, 2022)
This experimental research focuses on teaching emotional English intonation with video at university as this issue is not presented in scientific literature. The article aims to show a practical approach to teaching English intonation with ICT tools confirmed experimentally and in practice while conducting an English Phonetics course at university. The article is based on the author's dissertation «Teaching emotional intonation with video (2-nd year students at Linguistic University)» (2009). Reaviling linguistic and psychological features of emotional intonation the article shows that emotional intonation teaching is a complex phenomenon including a system of interdependent features - linguistic, paralinguistic and extralinguistic. This approach to teaching intonation provides equal conditions for students with the visual and auditory types of speech information perception to perceive and recognise emotional intonation patterns in communication. Educational video courses are considered beneficial to demonstrate verbal and non-verbal features of emotional intonation in a communicative environment. Besides, the article presents step-by-step teaching of emotional intonation based on carefully designed exercises: pre-communicative (receptive: recognition, differentiation and reproductive: imitation, imitation with a key, substitution, transformation, sounding) and communicative (productive: sounding and dramatisation); paused and synchronous. The examples of exercises with detailed descriptions of activities are displayed as well. Furthermore, a model of teaching emotional intonation shows stages of using video and performing communicative activities. After experimental learning, all 60 (100%) students achieved proficiency levels, primarily «proficient», and «advanced». The research has demonstrated that the proposed method of training can result in better recognition and more accurate production of emotional intonation in speaking.